Urgensi Mahkamah Konstitusi dalam Proses Pemberhentian Presiden - Riri Nazriyah (Fakultas Hukum Universitas Islam Indonesia, 2003)
The existence of Constitution Court as the pioneer of constitution in Indonesia must be warmiy responded, because through this board it will be found the solution from the jurisdictive aspect when the institutional conflict of arise-between House of Representatives and President which start from the House of Representatives' ideas thatPresident or the vice President has broken the iaw.